Variation of Phyllocnistis citrella population and parasitism in citrus cultivars under organic management - Efrom, Caio F.S.; Redaelli, Luiza R.; Diefenbach, Lúcia M.G. (CATIE, Turrialba (Costa Rica), 2015)
Aspects of population dynamics of Phyllocnistis citrella (Lep.: Gracillaridae), the citrus-leafminer, were evaluated by fortnightly samplings from July/2004 to June/2005 in two organically managed orchards, one of tangerine Montenegrina cultivar (Citrus deliciosa) and the other of the tangor Murcott (Citrus sinensis x C. reticulata), in Montenegro (29°37’51"S, 51°28’10"W), RS. In laboratory, the number of leaves, mines, eggs, caterpillars and pupae of P. citrella and of parasitoids were registered from each shoot. The colonization pattern and resource usage by the miner was similar in the orchards. The higher densities of mines, eggs, caterpillars and pupae of P. citrella were verified in summer and autumn. The average number of adults and immature was similar between cultivars. About 60% of the annual shooting escape from the miner attack. The parasitism was 23.3% in 'Montenegrina' and 24.9% in 'Murcott'. The drought periods along the study may have influenced the miner and parasitoid populations.